2014
DOI: 10.1149/2.0151413jes
|View full text |Cite
|
Sign up to set email alerts
|

The Versatile Electrocatalytic Oxidation of Glucose on Bimetallic Nanoparticulate Film Electrode

Abstract: Electrocatalysis at nanoparticles modified electrode has recently received huge attention because of the development of new sensors and energy conversion systems. The employment of two metals, with different catalytic properties are sometimes superior from the point of view reaction efficiency and overpotential decrease. Here, we demonstrate how electrocatalytic behavior of bimetallic noble metal nanostructures prepared from two types of nanoparticles are superior as compared with prepared from single type nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…−0.4 and −0.8 V at AuNPs/pectin and PtNPs/pectin, respectively, is visible (Figure ). Interestingly, when a mixture (1:1) of AuNPs/pectin and PtNPs/pectin solutions was used for electrode modification, an almost 10-fold increase of the oxidation current as compared to the PtNPs/pectin-modified electrode was observed without any overpotential loss, indicating the synergistic effect …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…−0.4 and −0.8 V at AuNPs/pectin and PtNPs/pectin, respectively, is visible (Figure ). Interestingly, when a mixture (1:1) of AuNPs/pectin and PtNPs/pectin solutions was used for electrode modification, an almost 10-fold increase of the oxidation current as compared to the PtNPs/pectin-modified electrode was observed without any overpotential loss, indicating the synergistic effect …”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, when a mixture (1:1) of AuNPs/pectin and PtNPs/pectin solutions was used for electrode modification, an almost 10-fold increase of the oxidation current as compared to the PtNPs/pectin-modified electrode was observed without any overpotential loss, indicating the synergistic effect. 64 The PdNPs/pectin-modified carbon felt electrode was tested for the electro-oxidation of formic acid (FA). 65 Anodic current related to the FA oxidation with the onset potential at −0.2 V is visible (Figure 10), and it is absent for the unmodified electrode.…”
Section: Curves B−e)mentioning
confidence: 99%
“…Studies have shown that Cu and Ni-based nanomaterials (such as nanoparticles [22], nanowires [23], MOF [24][25][26] and others [27]) have an obvious electrocatalysis on glucose. To make use of the synergistic effect of multiple metal-based nanomaterials, the researchers prepared catalysts with higher electrocatalytic activity and stability by doping metals with other elements [28][29][30][31] or organically combining them with different nanomaterials [32][33][34]. Since the direct electrodeposition method has the advantages of obtaining nanomaterials with various sizes and shapes, simple process, low cost and high efficiency, the preparation of composite catalysts by electrodeposition method is an attractive technique in the field of sensor fabrication.…”
Section: Introductionmentioning
confidence: 99%
“…However, the instability, critical operating conditions, and limited lifetimes of enzymes hinder the application of this biosensor for continuous glucose monitoring (Zhang et al, 2013). To address these drawbacks, non-enzymatic electrochemical glucose biosensors, including noble metallic materials and their alloys, have been proposed and developed (Dolinska et al, 2014;Chang et al, 2015;Shen et al, 2015;Ye et al, 2015;Wei et al, 2018;Karimi-Maleh et al, 2020b). However, the cost of noble metals was high.…”
Section: Introductionmentioning
confidence: 99%